Association between healthy lifestyle and memory decline in older adults: 10 year, population based, prospective cohort study. (25th January 2023) - Jia, Jianping; Zhao, Tan; Liu, Zhaojun; Liang, Yumei; Li, Fangyu; Li, Yan; Liu, Wenying; Li, Fang; Shi, Shengliang; Zhou, Chunkui; Yang, Heyun; Liao, Zhengluan; et al.
Abstract: Objective: To identify an optimal lifestyle profile to protect against memory loss in older individuals. Design: Population based, prospective cohort study. Setting: Participants from areas representative of the north, south, and west of China. Participants: Individuals aged 60 years or older who had normal cognition and underwent apolipoprotein E (APOE) genotyping at baseline in 2009. Main outcome measures: Participants were followed up until death, discontinuation, or 26 December 2019. Six healthy lifestyle factors were assessed: a healthy diet (adherence to the recommended intake of at least 7 of 12 eligible food items), regular physical exercise (≥150 min of moderate intensity or ≥75 min of vigorous intensity, per week), active social contact (≥twice per week), active cognitive activity (≥twice per week), never or previously smoked, and never drinking alcohol. Participants were categorised into the favourable group if they had four to six healthy lifestyle factors, into the average group for two to three factors, and into the unfavourable group for zero to one factor. Memory function was assessed using the World Health Organization/University of California-Los Angeles Auditory Verbal Learning Test, and global cognition was assessed via the Mini-Mental State Examination. Linear mixed models were used to explore the impact of lifestyle factors on memory in the study sample. Results: 29 072 participants were included (mean age of 72.23 years; 48.54% (n=14 113) were women; and 20.43% (n=5939) were APOE ε4 carriers). Over the 10 year follow-up period (2009-19), participants in the favourable group had slower memory decline than those in the unfavourable group (by 0.028 points/year, 95% confidence interval 0.023 to 0.032, P<0.001). APOE ε4 carriers with favourable (0.027, 95% confidence interval 0.023 to 0.031) and average (0.014, 0.010 to 0.019) lifestyles exhibited a slower memory decline than those with unfavourable lifestyles. Among people who were not carriers of APOE ε4, similar results were observed among participants in the favourable (0.029 points/year, 95% confidence interval 0.019 to 0.039) and average (0.019, 0.011 to 0.027) groups compared with those in the unfavourable group. APOE ε4 status and lifestyle profiles did not show a significant interaction effect on memory decline (P=0.52). Conclusion: A healthy lifestyle is associated with slower memory decline, even in the presence of the APOE ε4 allele. This study might offer important information to protect older adults against memory decline. Trial registration: ClinicalTrials.gov NCT03653156 .